(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Water is one of the most important natural resources, and as a resource to any nation, it should be well-planned, developed, conserved, distributed, and managed. Its infrastructure should also be properly maintained to avoid future water problems. This project sought to evaluate the water infrastructure in Lokoja with a focus on identifying areas requiring improvement. The scope of the study encompassed mapping the primary water pipeline distribution network and gathering geometric and attribute data concerning storage tanks and reservoirs within the designated area. Employing a combination of remote sensing and ground survey techniques, data was collected and utilized to generate a detailed spatial distribution map illustrating the major water supply networks and reservoirs. ArcGIS 10.2 was utilized for data processing and analysis, with the 3D analyst tool utilized to generate an elevation map and ascertain optimal site selection for gravity reservoir placement. The outcomes of the analysis included a visual representation of major pipeline connections, the precise location of tanks and reservoirs, and a comprehensive database containing both location and attribute information for these structures within the study area. The study findings revealed a pressing need for enhancing maintenance practices for water reservoir tanks, as a significant portion were found to be in substandard condition. Additionally, the study highlighted the necessity for pipeline extension to incorporate newly developed suburban areas within the study vicinity. The collated data serves as a pivotal resource for informed decision-making regarding the establishment of new reservoirs and the expansion of existing pipeline networks. Overall, this...